Implementasi Model Pembelajaran Matematika Realistik (PMR) dalam Meningkatkan Pemahaman Matematis Siswa Kelas VI MIN 2 Kota Mataram - Khairunisa Khairunisa; Wahyu Zikria Utami; Nisa Lestari; Djuita Hidayati (Universitas Maritim AMNI Semarang, 2024)
This research is based on the importance of learning realistic mathematics in mathematics. The purpose of this study is to determine the implementation of learning by using realistic mathematics learning models in improving the mathematical understanding of students of class VI MIN 2 Mataram City. PMR is a learning approach to mathematics that involves the reality and experience of students. In mathematics learning students are required to be more active in finding and finding solutions to a problem, so that learning that occurs will be centered on students. The research method used is a qualiative method for collecting data through observation, interviews and documents. The results showed that the application of realistic mathematics learning was effective in increasing students' mathematical understanding in the discovery of mathematical concepts through contextual learning and relevant to daily life. Thus, this research provides a significant involvement in understanding the role of PMR in increasing the mathematical understanding of students as well as part of an effective mathematical learning approach.